Pengaruh Pendekatan Realistic Mathematic Education Terhadap Kemampuan Berpikir Kreatif Siswa di Kelas VII SMPN Kecamatan Sungai Penuh - Leni Agus Meria (Sustainable, 2023)
The problem in this research are students’ creative thinking in mathematics. The design of research that used was combination between Quasi Experiment research and descriptive research. The research sampling was the students at grade VIIC SMPN 9 Sungai Penuh as experiment class and VIIE SMPN 2 Sungai Penuh as control class. Technique of data analysis was used Mann Whitney (Statistic U) test and the second hypothesis was used t-Test formula. Based on the research finding was gotten some conclusion. (1) the students’ skill of mathematic creative thinking that was taught by realistic mathematic education approach better than the students’ skill of mathematic creative thinking that was taught by learning conventional, (2) the students’ skill of mathematic creative thinking, (3) the students had have skill creative thinking after taught by realistic mathematic education approach by create some idea, not only focus on one way, had self way, and could do elaboration.